Land Dispute between Community and PTP Nusantara XIV In Central Maluku District - Jeter Donald Siwalette (Budapest International Research and Critics University, 2022)
This study aims to look at the factors that cause disputes between PTP Nusantara XIV and the people of Tananahu Village in Central Maluku Regency and provide solutions to resolve them. The research used qualitative methods, the data was carried out by means of observation, interviews using snowball sampling techniques and documentation, the informants interviewed were: community, community leaders, village government, employees and management of PTP Nusantara XIV. The research found that 3,458 ha of land disputes between PTP Nusantara XIV and the community of Tananahu Village were; socio-economic and regulatory factors lead to territorial claims, the proposed solution for dispute resolution between PTP Nusantara XIV and the people of Tananahu Village must be negotiated and mediated by involving the community who owns the land, community leaders, religious leaders, village government, Central Maluku Regency Government, Maluku Regency DPRD Middle with the Management of PTP Nusantara XIV.